Managerial economics - Png, Ivan, 1957- (New York, NY : Routledge, 2022)
"Now in its sixth edition, Ivan Png's Managerial Economics has been extensively revised with an introductory chapter emphasizing decision-making and behavioral biases, intensive application to current business and economic issues including technology, globalization, and pandemics, a closing chapter highlighting business responses to climate change, as well as a streamlined presentation focusing on the economics that managers need to know. As always, the text presents the key concepts of microeconomics intuitively, without sophisticated mathematics. Throughout, it emphasizes actual management applications. The new sixth edition is updated with fresh up-to-date vignettes and discussion questions from all over the world and enhanced with detailed instructor supplements. It is an ideal text for any course focusing on the practical application of microeconomic principles to management. Truly useful economics for managers. In the words of one professor, "I can use your book for serious conversation with adult students.""--
Revised edition of the author's Managerial economics, 2016.
Includes bibliographical references and index.
Keywords: Managerial economics